DIABETES MELLITUS TIPO 1 EM UMA DASCHUND - Da Silva, Luana Silva; Beck, Cristiane; Teichmann, Cristiane Elise (Salão do Conhecimento, 2018)
Relato de caso supervisionado realizado no curso de Medicina Veterinária da Unijuí